Investigating microfiltration membrane fouling via network modeling and optical coherence tomography - Han, Qi (Nanyang Technological University, 2020)
The inevitable membrane fouling during membrane filtration processes hinder the further application of membrane technology. Developing techniques for effectively mitigating membrane fouling relies on an in-depth understanding of the fouling mechanisms. This study proposes a two-dimensional network-based approach where the membrane was discretized and the fate of each particle was monitored individually, to explore the underlying external fouling mechanisms during dead-end microfiltration using polycarbonate track-etched membrane with cylindrical uniform pores. Three fouling parameters, namely the probabilistic factor for deposition in the non-porous area (β), the initial cake resistance (Rc0), and the specific cake resistance with respect to cake thickness (Rc’), can be obtained to characterize the fouling behavior by best-fitting the experimental flux-decline data to the network model. In parallel to theoretical study, advanced membrane fouling characterization technology, namely three-dimensional optical coherence tomography (OCT) scanning also applied to investigate fouling mechanisms. Online non-invasive OCT technique was applied to characterize the BSA protein fouling development on three different kinds of membranes with similar vendor-given pore size and porosity and a layer-based OCT image analysis method was established. The results showed that OCT is able to successfully reveal the external and internal fouling, however the implementation of quantitative comparison of protein internal fouling among the membranes was impossible from OCT results. The coupling of the network model and OCT characterization was employed to investigate the effect of the surface charged of monodisperse particulate foulants on cake formation and the fouling cake evolution of bidisperse suspensions in dead-end microfiltration. The results showed for the negatively charged polycarbonate track-etched membrane, negatively charged latex tended to deposit on the pore and form cluster due to repulsive particle-membrane electrostatic interactions. The bidisperse feeds with low mass ration of large particles tended to form homogeneous cake but the presence of a higher concentration of large particles lead to heterogeneous cakes; the presence of a lower concentration of large particles enhanced clustering while a higher concentration reduced that.